(untitled) (Prilozi za orijentalnu filologiju, 2017)
There are many manuscript works from which we can study the Sarajevo everyday life in the early 19th century. One of them is the work Târîk-i Enverî / Enveri's History ( تاريخ انورى ) by Muhamed Enveri Kadić, known as A Chronicle. It is considered as one of the prime sources for the study of the cultural history of Bosnia, in particular of Sarajevo from 1800 to1878. The paper brings individual notes about contracting marriages at the Sarajevo Shari'a Court from 1800 to 1810 made by Muhamed Enveri Kadić in A Chronicle. There are 67 such notes altogether (58 about Muslims and 9 about non-Muslims). From 11 Sarajevo court registers deposited at the Gazi Husrev-bey Library (reg. no. 39 to 50), Kadić took a significant number of the said notes, mostly about marriages of distinguished persons in the mentioned period. Among the many pieces of information, there are a number of notes about marriages contracted between non-Muslims, i.e. marriages of Catholics and Orthodox Christians contracted before qadi. A marriage could have been contracted also before deputy qadi (naib) or, with qadi's permission, before the imam to whose congregation the bridegroom belonged, with obligatory court registration. From the examples given in our paper, we can see that the amount of mehr-i muedžel was different, in compliance with bridegroom's social status, while for Catholics and Orthodox Christians it was smaller than for the Muslims. As in Islam wedding is not a religious act but rather making a civil private-law contract, it is not surprising that some Christians also decided to get married before quadi. Reasons for such a decision were of various nature.